Surgical ablation in patients with atrial fibrillation and left ventricular dysfunction: A systematic review and meta-analysis - Leo Noanh Consoli; Eren Cetinel; Mir Wajid Majeed; Pawel Lajczak; Ilias Georgios Koziakas; Prajna Wijaya; Alexandros Apostolou; Raheel Ahmed; Konstantinos Perreas (International Journal of Cardiology: Heart & Vasculature)
Background: Atrial fibrillation (AF) and left ventricular dysfunction (LVD) are common conditions that often coexist, with about 25% of patients in NYHA classes I-II having AF. Efficacy and safety of surgical ablation (SA) in this population remains unclear. Methods: We aimed to perform a single-arm meta-analysis to assess the outcomes of standalone and concomitant SA in adult patients with AF and LVD. We searched PubMed, Scopus and the Cochrane Library. Endpoints of interest were maintenance of sinus rhythm, freedom from anti-arrhythmic drug (AAD) use, change in LVEF, 30-day mortality, 1 year mortality and major procedural complications. We calculated pooled proportions or means for binary and continuous endpoints, respectively, with a 95 % confidence interval (CI). Results: Ten observational studies comprising 863 patients (mean follow-up of 19 months) were included. At 1 year, SA resulted in a sinus rhythm rate of 83.9 % (95 % CI: 69.5–92.3); freedom from AAD use of 81.6 % (95 % CI: 64.7–91.7); and mortality of 5.77 (95 % CI:3.7–8.9). 30-day mortality was 2.16 % (95 % CI: 0.9–4.9); major complications 16.73 % (95 % CI: 12–23); and an improvement in LVEF of 12 % (95 % CI: 9–17). Conclusion: This meta-analysis found that SA appears to be an effective strategy to achieve sinus rhythm in patients with AF and LVD, with a pooled 30-day mortality of 2.2%. Comparative studies are warranted to evaluate the relative safety and efficacy of SA compared with other rhythm control strategies in this population.